The Study of Social Welfare Management for the Elderly in Kamphaengdin Sub-district Administrative Organization, Sam Ngam District, Phichit Province - Insuk , Rattikarn; Rojanatrakul, Tanastha (Journal of Modern Learning Development, 2021)
This research study aims to study the opinions of the elderly on social welfare provision. To compare opinions of the elderly towards social welfare management in and to study guidelines for social welfare management for the elderly in Kamphaeng Din Sub-District Administrative Organization, Sam Ngam District, Phichit Province. This research study was conducted in accordance with quantitative research methodology and qualitative research. The population and sample were 246 elderly subjects obtained by Taro Yamane’s formula representation and four key informants. The research instrument was a data analysis questionnaire using statistics, frequency, percentage, mean, deviation. Standardized t-test, F-test (One Way ANOVA) and interview form. Data analysis Using content analysis techniques, contextual content, information synthesis according to objectives. The results of the research were as follows: 1. Opinion of the elderly on social welfare arrangements for the elderly in Kamphaeng Din Sub-District Administrative Organization, Sam Ngam District, Phichit Province. Overall, the overall level was at a high level. 2. The comparative results showed that the elderly with different personal factors had opinions on the social welfare management system for the elderly in the area of ​​Kamphaeng Din Sub-District Administrative Organization, Sam Ngam District, Phichit Province. 3. Guidelines for the provision of welfare for the elderly must focus on the care and assistance. And develop the elderly by themselves Family and participation in both the sub-district administration organization and local agencies as follows: Social welfare arrangements for promoting the development of the well-being of the elderly by yourself. Social welfare provision for promoting the development of well-being of the elderly by their families. Social welfare provision for promoting the development of well-being of the elderly by local authorities. Social welfare provision for promoting the development of well-being of the elderly by the community.